Use of Targets to Improve Health System Performance: English NHS Experience and Implications for New Zealand - Nicholas Mays (New Zealand Government, The Treasury, 2006)
The setting of quantitative, time-limited ?targets? backed up by institutional and managerial rewards and sanctions has been a notable feature of performance improvement efforts in the National Health Service (NHS) in England since 1998 and especially in the period 2000-2004. Performance improved in the areas covered by English NHS targets, most markedly in relation to waiting times, but also in relation to treatment outcomes. None of the other parts of the United Kingdom followed England and similar trends were not observed, particularly not in waiting times, despite similar injections of funds. Despite the improvements in performance in target areas, targets were criticised, principally, for having perverse and unintended consequences (e.g. distorting priorities, encouraging ?gaming?, etc) which could have potentially out-weighed their benefits. On the other hand most experts in performance improvement in public services argue that carefully chosen, incentivised targets are a useful part of the performance management repertoire when used well (e.g. when sanctions and rewards are proportionate). Some dysfunctional consequences are to be expected, but can be mitigated. Given the similarities between the English NHS and the New Zealand public health system, there is scope to use targets and related incentives sparingly to improve performance in New Zealand in areas of high importance to government and the public.
Keywords: I18; 330; performance measurement; performance management; performance improvement methods; target-setting; control of public services